TEACHING METHOD IN WRITING DESCRIPTIVE TEXT (A Descriptive Study at the Seventh Grade Students of SMP Negeri 3 Klaten Academic Year 2016/2017) - anis uswatun khasanah (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Abstract: This research is aimed at finding the answer to the following research questions: (1) What is the method used by English teacher to teach writing descriptive text at seventh grade of SMP Negeri 3 Klaten Academic Year 2016/2017? (2) What are the problems faced by the English teacher in teaching writing descriptive text at the seventh grade of SMP Negeri 3 Klaten Academic Year 2016/2017? The objectives of the research are divided into three, there are writing, descriptive text and the method used by English teacher. This study used descriptive qualitative research. The researcher as a non-participant observer. The researcher did three times observation in VII H and doing interview with one English teacher to know about the method used by English teacher to teach writing descriptive text. The subject of the observation consists of 37 students from VII H in SMP Negeri 3 Klaten academic year 2016 / 2017. The instruments used to collect the data were observation, interview and study document (lesson plan, syllabus and student work sheets). The researcher did three steps to analyze the data. There are the data reduction, the data display and the verify conclusion. The researcher use triangulations as a trustworthiness of the data.The finding of the research showed that the teacher did on the first and the second meeting was all in line to the frame work of task-based language teaching. There were three stages in implementing task-based language teaching in a classroom, which they were the pre task stage, the task cycle and the language focus. The problems were the student lack of vocabulary and did not know how to use the appropriate verb in the sentences. The teacher gave tasks to increase the student vocabulary and know how to use the appropriate verb in the sentences. The models of the tasks were matching, whether is it right or wrong. Beside this, the teacher taught step by step so that the students can understand about the lesson, especially writing descriptive text.